The state and development trends of social science education in Russia - Rezeda Ilgizovna Khoraskina, Rimma Gabdarxakovna Shamsutdinova, Elena Mikhailovna Shuvalova,; Kozlova, Yulia Alexandrovna (Opción, 2019)
This publication is devoted to the identification of the features of the development state and trends of social science education in Russia (90-ies of XX century – the beginning of XXI century) via the methods of determinism and system analysis. As a result, the beginning of system reforming of social studies education in Russia coincided with the period of systemic crisis. In conclusion, the new (second) generation standard, known as the GEF and aimed to a system-activity approach in the study of school disciplines was accepted in 2012 and is the basic at the present time.